2016
DOI: 10.1017/s0007114516002257
|View full text |Cite
|
Sign up to set email alerts
|

Changes in fruit, vegetable and juice consumption after the diagnosis of type 2 diabetes: a prospective study in men

Abstract: Given the importance of prevention of complications in type 2 diabetes (T2D), we aimed to examine changes over time in consumption of fruits, vegetables and juice among men who were diagnosed with T2D in comparison with men without diabetes. The prospective Cohort of Swedish Men, aged 45-79 years in 1997, was used to examine changes in diet after diagnosis of T2D. Dietary intake was assessed using FFQ in 1997 and 2009. In all, 23 953 men who were diabetes free at baseline (1997) and completed both FFQ were eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
(67 reference statements)
0
12
0
2
Order By: Relevance
“…However, the FFQ used in this study had a relatively high validity. Moreover, consumption of fruits and vegetables in the studied cohort was relatively stable between 1997 and 2009 (increased only by 0.7 serving/week) 36. Nevertheless, any misclassification of fruit and vegetable consumption, because of the prospective design, would be non-differential and most likely have attenuated rather than exaggerated the true associations.…”
Section: Discussionmentioning
confidence: 85%
“…However, the FFQ used in this study had a relatively high validity. Moreover, consumption of fruits and vegetables in the studied cohort was relatively stable between 1997 and 2009 (increased only by 0.7 serving/week) 36. Nevertheless, any misclassification of fruit and vegetable consumption, because of the prospective design, would be non-differential and most likely have attenuated rather than exaggerated the true associations.…”
Section: Discussionmentioning
confidence: 85%
“…The interpretation regarding causality between vegetable intake and T2D should nevertheless be done with great caution, as one can only infer causality with certainty from randomised controlled trials (42) . Moreover, a misclassification between T2D and latent autoimmune diabetes of adults (43) , and of type 1 diabetes as T2D and vice-versa might have occurred. One major problem is the high rate of undiagnosed disease as about one-third of all diabetics have not yet received a diagnosis (19) .…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…As dietary vitamin C contributes to plasma vitamin C concentrations, potential differences in the intake between those with normal glucose control and T2DM must also be considered. A prospective study of 48,850 men revealed that while the baseline consumption of fruit and vegetables was similar, men who developed T2DM increased their consumption of fruit and vegetables by 1.6 serves/week compared to an increase of 0.7 serves/week in those who remained diabetes free [ 12 ]. Therefore, it seems that people with T2DM are altering their diet in an attempt to manage their blood sugar.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, clinical advice to those newly-diagnosed with T2DM focuses on improving the diet. However, the dietary changes appear to be small and, furthermore, those with T2DM appear to have a similar intake of fruit and vegetables to those without T2DM [ 12 ].…”
Section: Introductionmentioning
confidence: 99%